Pengaruh Abu Janjang Kosong Kelapa Sawit dan Mikoriza Terhadap Pertumbuhan dan Hasil Bawang Merah Pada Ultisol - Kristoni Purba; Budiyati Ichwan; Heri Junedi (Jurnal Media Pertanian, 2026)
Shallot is one an important of vegetable comodity, both in economic value and nutrition ingredients. One of an effort to support the increasing of shallot yield with plantation technology by giving palm oil ash fertilizer and micorrhiza. The experiment we studied to find out the effect of palm oil ash fertilizer and michorrhiza with different doses on yield of shallot. The experiment used Randomized Block Design consisted 4 doses of palm oil ash a0 : 0 ton-1ha,a1 : 2 ton-1 ha, a2 : 4 ton-1 ha, a3 : 6 ton-1 ha and michorrhiza ,m1 : 0 g plant-1, m2 : 5 g plant-1, m3 : 10 g plant-1 m4 : 15 g plant-1 with 3 replication. Observation parametrs include plant height, number of leaves per clump, number of tubers per clumb, fresh tuber weight per clumb, dry tuber weight per clump, average weight per tuber and average tuber weight per hectare. The data were analyzed using a Randomized Block Design at the 5% level using DStaat version 1.514 and SPSS Statistic 22, and then differences between treatments using the LSD (Least Significant Difference ) test at the 5% level test. The results show that dose of 2 ton-1 ha oil pam ash fertilizer alone has a very significant effect on height plant at 5,6 and 7 weeks after planting and the number of leaves at 3,4 and 7 weeks after planting, wet and dry tuber weight and average weight per dry tuber and weight per hectare.